Effect of grazing on the composition and floristic diversity during fallow at El-Tarf, Algeria - Matallah, Saida; Matallah, Fouzi (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
In the El-Tarf region, located in northeastern Algeria, fallow lands are frequently used as grazing grounds for sheep flocks, where they are left all day with a significant grazing load. Limited studies conducted to assess the effects of grazing have yielded varied and sometimes contradictory results, thus underscoring the need for reliable local data. The study aims to assess the impact of grazing on the floristic richness, diversity, production, and chemical composition of fallow lands in the El-Tarf region (northeast Algeria). Measurements were taken during the optimal vegetation period from March to June over a period of 2 years (2019 and 2020). The experimental design included a single factor: grazing intensity (no grazing, moderate grazing, and intense grazing). The results indicated that grazing reduced floristic richness and diversity (Maximum Diversity, Shannon and Weaver Index, Evenness Index), but it did not have an effect on coverage. The non-grazed fallow land is richer, hosting 23 herbaceous species distributed among 8 botanical families, with the most represented being Asteraceae (39 %), followed by Poaceae (26 %). The Fabaceae, on the other hand, display a more modest representation, accounting for only 13 %.Grazing also decreased significantly the biomass and total aboveground herbaceous phytomass, with improvements noted in non-grazed conditions, recording values of 3.80 t.DM.ha-1 and 1.77 t.DM.ha-1, respectively. In addition, grazing had a significant impact on chemical composition, with the highest values recorded for moderate grazing, reaching 14.7 % for total nitrogen content and 11.66 % for mineral content.